The reductive decyanation reaction: an overview and recent developments - Mattalia, Jean-Marc R. (Beilstein Journal of Organic Chemistry, 2017)
This review presents an overview of the reductive decyanation reaction with a special interest for recent developments. This transformation allows synthetic chemists to take advantages of the nitrile functional group before its removal. Mechanistic details and applications to organic synthesis are provided.
Keywords: α-aminonitrile; decyanation; electron donor; hydride; malononitrile; transition metal catalysis